ADAB DALAM BERBEDA PENDAPAT DALAM ISLAM MENURURT TAHA JABIR AL-ALWANI: STUDI ANALISIS KITAB MIN ADAB-I AL-IKHTILÄ€F ILÄ€ NABDZI AL-KHILÄ€F - Affan, Mohammad Husnul (ISLAMIKA, 2021)
Human is the creation that Allah created with the reason to think and contemplate. Nevertheless, each reason has produced a difference of thought and ideas. Then, Islam was a religion from the rise of Muhammad as the Messenger completely accommodated in any of diversity, for instance, races, languages, thoughts, and ideas. Taha Jabir Al-Alwani explicitly explains how is the difference in Islam and how Muslims can solve it. Historically, the differences were not a new discourse worldwide, but it started east a long ago. However, the Prophet Muhammad and his companions succeeded in setting an example to leave this case of difference of opinion. So, this article will discuss the concept of differences in Islam, the kinds of differences in Islam, the adab of dealing with differences, and strategies to avoid differences.